change in capital expenditures And its impact on the profitability of pharmaceutical companies (Journal of the College of Basic Education, 2023)
The pharmaceutical industry is considered one of the strategic industries and has been able to growcontinuously and that this industry is characterized by characteristics and considering it from othervarious other industries, and therefore, when studying any subject related to the industryPharmaceutical industry should focus on a group of factors that make the industry distinct. We mention that it requiresA lot of money, a lot of time, and a lot of money.The second of these factors that distinguish it is that marketing plays a very important role inThe success of the pharmaceutical industries, and marketing in the pharmaceutical industries differs from marketingIn other industries, where marketing is considered an approved process in other industries.The most important factor in this process lies in the fact that the decision maker for the purchase of the drug is the doctor, and notThe patient (buyer) in addition to the high requirements in the competencies and skills of the workersIn pharmaceutical marketing, because medicine is an important commodity and cannot be compared with other commodities.Its marketing requires scientific knowledge of all its products. Pharmaceutical industries are also distinguished by their diversityproducts and the diversity of their assortments. The pharmaceutical industry market is a fiercely competitive market.The process of research, development and marketing plays a major role in controlling the market, so it is consideredInvestment decisions in this sector are of importance to both management and investors as they areIt involves a tangible change in capital expenditures, and because it is a decision, it is difficult to cancel its effect withoutSignificant losses and their expected impact on profits and future cash flows positively.